2019
DOI: 10.1051/shsconf/20197009011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rational psychotherapy on emotional state and cognitive attitudes of patients with neurotic disorders

Abstract: Development of a neurotic disorder is a result of the formation of the non-adaptive cognitive structures. Each structure conceptualizes the particular nature of perception, gained experience, specific features of the experience understanding, as well as human behavior. As a result of such cognitive structures, automatic thoughts, cognitive biases, and inadequate emotional sufferings occur that determine the choice of maladaptive behavioral strategies. Unconscious nonrational attitudes exacerbate the emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The results of the analysis of differences in the indicators of the emotional states, basic beliefs and attitudes of neurotic patients before and after undergoing treatment in a hospital, taking into account the types of neurotic disorders, are described in detail in our previous paper [26]; in this work, we consider it necessary to focus on the gender specificity of the dynamics of the studied indicators.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the analysis of differences in the indicators of the emotional states, basic beliefs and attitudes of neurotic patients before and after undergoing treatment in a hospital, taking into account the types of neurotic disorders, are described in detail in our previous paper [26]; in this work, we consider it necessary to focus on the gender specificity of the dynamics of the studied indicators.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proved that the art-therapeutic process contributes to the prevention of neurosis-like personality states, the elaboration and outpouring of negative emotions, internal contradictions, helps to increase the level of awareness of one's feelings, take control of them which provides relaxation, relieving of mental tension, increasing of self-esteem [19], helps with interpreting displaced experiences, accepting one's feelings and experiences [16]. Moreover, art therapy is effective in working with people experiencing crisis conditions, in correcting the consequences of psychotraumatic stress, therapy of mental disorders [20,21], in the medical and psychosocial rehabilitation of mental patients [22,23]. All these problems intensify the personality alcoholization.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the effectiveness of therapy is often determined by personality characteristics [15,16]. In the development of chemical addiction, the peculiarities of its course and the prognosis of the results of rehabilitation, the personality characteristics of addicts also matter.…”
Section: Introductionmentioning
confidence: 99%